Radial bisection of words and lines in right‐brain‐damaged patients with spatial neglect. Issue 3 (27th November 2015) - Veronelli, Laura; Arduino, Lisa S.; Girelli, Luisa; Vallar, Giuseppe
Abstract : The bisection of lines positioned radially (with the two ends of the line close and far, with respect to the participant's body) has been less investigated than that of lines placed horizontally (with their two ends left and right, with respect to the body's midsagittal plane). In horizontal bisection, patients with left neglect typically show a rightward bias for both lines and words, greater with longer stimuli. As for radial bisection, available data indicate that neurologically unimpaired participants make a distal error, while results from right‐brain‐damaged patients with left spatial neglect are contradictory. We investigated the bisection of radially oriented words, with the prediction that, during bisection, linguistic material would be recoded to its canonical left‐to‐right format in reading, with the performance of neglect patients being similar to that for horizontal words. Thirteen right‐brain‐damaged patients (seven with left spatial neglect) and fourteen healthy controls were asked to manually bisect 40 radial and 40 horizontal words (5–10 letters), and 80 lines, 40 radial and 40 horizontal, of comparable length. Right‐brain‐damaged patients with spatial neglect exhibited a proximal bias in the bisection of short radial words, with the proximal part corresponding to the final right part of horizontally oriented words. This proximal error was not found in patients without neglect and healthy controls. For bisection, short radial words may be recoded to the canonical orthographic horizontal format, unveiling the impact of left neglect on radially oriented stimuli.